The effectiveness of an agricultural policy tool: Business Plans in Fruit Trees - Tamosiunas, Martha (Agrociencia Uruguay, 2019)
In Uruguay, between 2006 and 2012, the so-called «Business Plans» (BP) were proposed as an instrument to support the Farm. The instrument allowed access to non-reimbursable funds, according to kilograms of fruit delivered, and to interest-free reimbursable funds for inputs and technical assistance. The objective was to evaluate the effectiveness of the BPs in facilitating the integration of family producers (FPs) into value chains. Non-experimental cross-sectional research was conducted on the 57 deciduous fruit plans approved between 2006 and 2012. The criterion of effectiveness is associated with evidence showing that FPs participate in repeated calls, have stable links with commercial agents, perceive the same benefits as non-family producers, and have a favorable opinion of the instrument. Quantitative information was analyzed through contingency tables with a significance level of 5 %. A total of 510 producers participated, of which 162 were FPs, and 203 million Uruguayan pesos (constant as of December 2016) were approved for the BP. It is concluded that the instrument was not effective in integrating FPs due to the lack of value chains that accept fruit produced with its technical restrictions. Despite the repeated participation of the FPs and their favorable perception, the appropriation of the benefits was dissimilar, benefiting only partially in financing inputs and technical assistance. For the FPs, marketing did not improve because they have difficulties in fulfilling contracts and the marketing chains in which they participate have antagonistic relationships.